La oferta laboral de los hogares en la Parroquia Sibambe Cantón Alausí, Análisis a partir de la Teoría de juegos. - Calle Angamarca, Yolanda Elizabeth (2023)
The objective of the research was focused on the assumption that households are in a constant decision-making process. However, seeking the common good and showing affection for each other does not make the individualism of rational beings any less critical. Thus, by means of a Stackelberg game, the couple's decisions were modeled by analyzing the population of the parish of Sibambe, Canton Alausí, where endogenous variables (each individual's actions) and exogenous variables (factors affecting the family) were considered as determining factors to choose the most optimal strategy in order to maximize their utility. Likewise, a Probit-Bivariate model was used to discard (exogenous) variables. Then, empirically, a Stackelberg equilibrium was obtained.